2015
DOI: 10.1124/jpet.115.225698
|View full text |Cite
|
Sign up to set email alerts
|

Metformin's Intrinsic Blood-to-Plasma Partition Ratio (B/P): Reconciling the Perceived High In Vivo B/P > 10 with the In Vitro Equilibrium Value of Unity

Abstract: Blood cells are considered an important distributional compartment for metformin based on the high blood-to-plasma partition ratio (B/P) in humans (.10 at C min ). However, literature reports of metformin's intrinsic in vitro B/P values are lacking. At present, the extent and rate of metformin cellular partitioning was determined in incubations of fresh human and rat blood with [14 C]metformin for up to 1 week at concentrations spanning steady-state plasma C min , C max , and a concentration associated with la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…where X erythro and X plasma are the amount of metformin in the erythrocyte and plasma compartment, respectively, and k in,RBC and k out,RBC are the partitioning rate constants of metformin from plasma to erythrocytes and from erythrocytes to plasma, respectively, and obtained in vitro by measuring time‐dependent blood cell distribution of metformin using human blood ( Table ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…where X erythro and X plasma are the amount of metformin in the erythrocyte and plasma compartment, respectively, and k in,RBC and k out,RBC are the partitioning rate constants of metformin from plasma to erythrocytes and from erythrocytes to plasma, respectively, and obtained in vitro by measuring time‐dependent blood cell distribution of metformin using human blood ( Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Metformin undergoes negligible hepatic metabolism, but it is mainly excreted intact into the urine; its renal clearance exceeds the glomerular filtration rate, indicating tubular secretion. With negligible plasma protein binding, metformin slowly distributes to erythrocytes . Metformin exists ionized at physiological pHs, relying on transporters for its translocation across cell membranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Xie et al (2015) recently reported a PBPK model for metformin in which the incorporation of plasma -blood cell distribution rate constants allowed recovery of both plasma and whole blood drug concentrations over an extended time. When a blood cell distribution compartment was incorporated into the metformin PBPK model of the current study (using a similar approach to Xie et al), simulated plasma metformin concentrations and the extent of the DDI with cimetidine were unaffected (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma binding of metformin is insignificant, so pregnancy‐induced alterations in plasma albumin levels are not expected to impact metformin disposition. However, metformin is a high extraction ratio compound in the kidney (Xie, Ke, Bowers, & Zamek‐Gliszczynski, ). Thus, pregnancy‐induced changes in metformin pharmacokinetics can be primarily attributed to increased renal blood flow, which increases both GFR and tubular secretion rate (Eyal et al, ), GFR is known to increase during the 1st trimester of pregnancy and to peak at mid‐pregnancy (↑37–45%), with a subsequent decrease in the last trimester (Tasnif et al, ).…”
Section: Discussionmentioning
confidence: 99%